P-180 Education beyond the walls: 3 hospices working together. Issue Volume 5: Issue (2015)Supplement 3 (1st November 2015) - Davies, Alison; Brown, Vanessa
Abstract : The Commission into the Future of Hospice Care sets out future ambitions for hospice care, whilst acknowledging the financial constraints faced around uncertain income. These challenges offer opportunities for hospices to work differently; one option is to work in collaboration. This new approach has the potential to have greater impact in supporting the education and facilitation of EoLC, whist strengthening a proactive educational framework that is shared across boundaries. This model has required three hospice managers to challenge traditional working in isolation, whilst acknowledging common areas around educational requirements for the development of their staff and the wider community. The presentation sets out to describe this evolving model of working; the hospices have grasped an opportunity that supports collaboration, whilst challenging traditional boundaries. This model looks at discouraging working in isolation, and seeks to uncover the true potential of hospices and the End of Life Partnership (EoLP), which has yet to be fully uncovered. The hospices, working in collaboration with the EoLP set out to develop an educational framework that is recognised across all three hospices and communities, enabling resources and specialist knowledge to be shared. The approach has enabled the hospices to recognise 'new' potential, sharing ambition and creativity in reaching a wider audience than they had done previously. They strive to lead this model of working forward, sharing the strength of collaborative working. Interest in this model has also raised interest from other hospices, we areseeing benefits in collaboration and partnership working. Hospices have a responsibility to develop their workforce whilst reviewing the way in which they support and educate the wider community. Hospices need to grasp opportunities for building a greater capacity to support education delivery that ultimately impacts on care delivery.